Development of an Online Store on the WordPress Platform: Functional Model and Practical Implementation - Ikramov, Asadbek; Akhmedova, Iroda (MMIT Proceedings, 2025)
This paper explores the development process of an online store based on the WordPress platform using the WooCommerce plugin. The project aims to deliver a functional, secure, and user-friendly e-commerce solution without substantial financial investment. The full development cycle is covered—from interface design to the automation of business processes. The results of usability and performance testing confirm the system’s stability and user convenience. The project highlights the importance of thoughtful UX/UI design and shows that modern tools are accessible even to small businesses and startups.